Desenvolvimento de metodologia analítica para determinação de íons cobre em aguardente empregando análise por injeção em fluxo com detecção quimiluminescente - Cruz, Sônia Maria da (2009)
This work proposes the determination of Cu2+ ions in samples of Brazilian sugar spirit (cachaça), using a flow injection analysis system coupled with chemiluminescent detection. The detection is based on the catalytic effect of Cu2+ ions on the oxidation reaction of the compound 3-Aminophthalhydrazide (luminol) by hydrogen peroxide in basic medium. The formation of unstable intermediate excited state was monitored in arbitrary unit of measure. The FIA system was coupled with a mini-column containing silica functionalized to pre-concentration the ions Cu2+, aiming to ensure greater selectivity and sensitivity. Studs were realized to optimization of experimental conditions of flow system and the parameters of better sensitivity and selectivity were selected. The curve of calibration was obtained and linear work range was 1,0 and 9,0 mg L-1 to copper ions with equation S = 5,3189 (± 0,2874)C + 0,1814(± 1,5255) and correlation coefficient (r) = 0,9992 and detection limit of 0,4024 mg L-1. The accuracy of proposed method was evaluated though eight consecutive injections of a standard copper ions containing 0,5 mg L-1. The activation of mini-column was performed after each eight cycle of pre-concentration with injection of 76,9 μL of hydrochloric acid solution across of mini-column. Each complete cycle of injection of sample and elution delay 10 minutes in proposed conditions. Regardless of large time for each cycle was relatively high, low concentrations can be detected by use of this proposed methodology and the use of mini-column pre-concentration improve great selectivity